Бәршемизге қәдирдан устаз еди (SCIENCE and SOCIETY, 2016)
The article deals with the biography and creation of the great composer Ganiybay Amaniyazov, his scientific works, creative musical works on different themes and their educational importance. The materials of the article may be used by the teachers in doing idependent work in specialty and at the lessons in preparing future teachers of music.